PTH-197 Significant reduction in catheter-related bloodstream infections in high risk adult patients on home pn or iv fluids after introduction of secondary prophylaxis with taurolidine-citrate line lock. (22nd June 2015) - Barnova, I; Fragkos, KC; Morgan, S; Smith, L; Saravanapavan, H; Samaan, M; Patel, PS; Keane, N; Babington, M; Di Caro, S; Rahman, F
Abstract : Introduction: Patients on home parenteral nutrition (HPN) or IV fluids are at risk of complications especially of catheter-related bloodstream infection (CRBI). The primary aim of this study was to compare the CRBI rate before and after introduction of secondary prophylaxis with Taurolidine-citrate line lock (TLL). Method: Data from 28 patients using TLL from one centre were collected retrospectively. The data collection was from patients' medical records at our centre and patients' interviews. CRBI rate was calculated per 1, 000 catheter days (CD) and p-value (Z-test) was used to assess significance. Results: Number of patients included into the study was 28. F:M ratio was 19:9 and the ratio of patients with short bowel syndrome to patients with dysmotility disorders was 9:5. Self/nursing administration ratio was 1:1. TLL was introduced on first patient in Sept 2007 and the last in May 2014. Results showed the CRBI rate of 6.8/1, 000 CD prior to introduction of TLL (142 CRBI in 20, 881 days) and 0.92/1, 000 CD post introduction of TLL (18 CBSI in 19, 642 days) with p-value of <0.001. 71.4% of patients were CRBI free after introduction of TLL (0 infections per 1, 000 CD), 21.4% TLL significantly improved CRBI rate by at least 50%. Self/nursing administration post TLL introduction did not show any significant difference (1.14: 0.98 CRBI/1, 000 CD with p-value 0.74). Patients with single lumen catheters had CRBI rate of 0.58 per 1, 000 CD after TLL use and patients with double lumen catheters had CRBI rate of 1.2 per 1, 000 CD with p-value of 0.176. There was no significance in CRBI rate of patients with stoma/fistula compared to patients without stoma/fistula pre and post introduction of TLL. The p value for CRBI pre TLL introduction was 0.58. The p value post TLL introduction was 0.67. The highest rate of CRBI after introduction of TLL was recorded in patients using HPN for 7/7 + IV fluids and meds which (2.1 per 1, 000 CD) and the lowest rate was recorded for patients using PN less than 7 days or using only IV fluids 0 per 1, 000 CD (Table 1 ). Conclusion: The data suggest that secondary prophylaxis with TLL significantly decreases the CRBI rate in selected high-risk patients. Disclosure of interest: None Declared.